HISTORIOGRAFIA E PRÁXIS: REFLEXÕES SOBRE OS PRESSUPOSTOS DA DIDÁTICA DA HISTÓRIA EM CAIO PRADO JÚNIOR - Dalazona, Flávio José (2020)
The present study aims at investigating the didactic function of the historical constitution of meaning based on historiography. We comprehend that the History Didactics field is situated as a subdiscipline of historical science that, a priori, investigates the historical learning processes aroused by historical consciousness. The discussions on History Didactics (Geschichtsdidaktik) commenced in Germany betweenthe 1960s and the 1970s. Mainly around Jörn Rüsen’s considerations, we pursue to interpret Caio Prado Júnior historiographical production about the Brazilian past and how his historiographical thinking is tangled in a project to align Brazilian historical consciousness; therefore, we take Caiopradian historiographical production as an object of research. The problem centers on how didactic dimensions are presented in the production of historical knowledge considering the temporal orientation function that historical science itself is a constituent of. It is understood that the historical narrative is written in a specific space, that is, a locus delimited from the production of knowledge about human actions in time. We seek to reconstruct, in this way, the relationship between historiographic discourse and society, thus rescuing the currentness of Caio Prado Júnior thought about the Brazilian revolution as a guide to our identity. Based on the theory of History Didactics, it is understood that Marxist historiographical production inaugurates a new chapter in the historiographic trajectory of the Brazilian historical process and a new milestone in the conception of meaning and function on the meaning of our past.